NEW APPROACH OF SCIENCE: PICOSCIENCE AND PICOTECHNOLOGY - MANISH KUMAR; VIJAYA TRIPATHI (International Journal of Pharma and Bio Sciences, 2014)
Picotechnology is engineering at the molecular (groups of atoms) level that involve the manipulation of matter at the smallest scale (10−12). At this very small scale (Pico), the properties of materials such as colour, magnetism and the ability to conduct electricity change in unexpected ways. Picotechnology is used in instrumentation, photochemistry, chemistry, biochemistry, microbiology, molecular biology and developmental biology etc. The products of science can have common examples in fuel cells, fabrics or drug design. The picoscale particles can be encapsulated more precisely within polymers and can be functionalized with protein or nucleotides. The temperature, humidity, electricity and their regulatory factors play a significant role in biomedical, automotive actions of biomolecules in the environment. The proteins and their regulatory metal cofactors also play a significant role in structural-functional actions of biomolecules in the body, those analysis/measurements becomes a possible with Picoscience.